Implementasi Metode Markerless Augmented Reality Untuk Memvisualisasikan Informasi Kain Batik Berbasis Android (Studi Kasus Kampung Batik Kauman) - Bayu Tri Pamungkas; Mochamad Adhari Adiguna (CV. Multi Kreasi Media, 2022)
The culture of wearing batik cloth in Java was born from the palace environment, which complements it with a philosophy of life: a blend of dimensions, art, customs, outlook on life, and personality. In short, batik was born not just as a commercial object, but as a part of life. The motifs on batik cloth are inspired by the beliefs of the people who made the cloth.These various motifs will also be influenced by the characteristics and meanings to be conveyed from each region. At this time, the information media for visualization of batik cloth is still lacking because it is only in the form of pictures and sheets of cloth, making it difficult for us to know the details of the actual batik cloth information. There are several ways to preserve batik, one of which is by providing information about batik cloth by utilizing augmented reality technology. Augmented Reality (AR) is a 3D technology that can make it easier to explain an object or image in detail. AR can be used to help visualize abstract concepts for understanding and structuring an object model. In this study, the authors created an augmented reality application to visualize batik cloth information. The method used in this research is markerless augmented reality. The application being created will be implemented on an Android-based smartphone/tablet. With this application, it can make it easier for the public to receive fabric information in the form of batik names, batik patterns, and a brief history of batik in the Kauman batik village.